Analysis of Innovation, Proactive, and Risk Taking as Presentations of Entrepreneurial Orientation towards Business Success of Second and Third Generation Family Business in Indonesia - Utami, Christina Whidya; Tambunan, Damelina; Padmalia, Metta (Jurnal Entrepreneur dan Entrepreneurship, 2021)
Research Objective: To analyze the effect of entrepreneurial orientation towards the business success of second and third generation family businesses in Indonesia. Methodology/ Research Approach: This study used a cross-sectional, correlation research design. The survey was conducted to 153 medium-scale family businesses that have run for 5-50 years and categorized as middle-scale business ran by the second and/ or third generation family. Hypothesis testing was done via a multiple regression using SPSS. Findings: there is a significant effect between entrepreneurship orientation, which is the independent variable of this study, that covers three indicators namely innovation, proactive, and risk-taking abilities. Innovative and proactive have a significant and positive effect, while risk-taking ability has a significant and negative effect on the success of family businesses in Indonesia. Research limitation/ implication: This study investigates strategies that family businesses use, in terms of entrepreneurial orientation. The limitations of this study are: Bias in assessment perspective of fellow families and the scale of the family business only focus on second and third-generation middle-scale family business. The implication of this research is to create an entrepreneurial orientation culture in family businesses that tend to be lacking innovative, proactive, and risk-taking behaviors, considering the amount of interference and involvement of family members in the management of their family businesses. Practical implication: It is hoped that the second and the third-generation family members show a better perspective exploration in seeing whether entrepreneurial orientation has been implemented and has an impact in creating business success. Thus, family businesses are expected to scale-up their businesses into large-scale companies, and at the same time, survive the succession phase of the next generation. Originality/ value: This study offers an analysis of a unique entrepreneurial orientation, given the personality, family, ownership, and management system in family businesses in Indonesia are different from other countries. Besides, there are influences of technological advances that may interfere family businesses, particularly the family system, in Indonesia